Literatur Riview Kepatuhan Wajib Pajak Orang Pribadi: Pengaruh Literasi Pajak, Teknologi, dan CoreTax - Nurul Fitri Afifah; Oryza Tannar (Prosiding Seminar Nasional Ilmu Manajemen Kewirausahaan dan Bisnis, 2026)
Taxpayer compliance is a key factor in optimizing state revenue, given that taxes are the primary source of funding for various national development programs. However, in practice, Indonesia still faces various challenges in improving taxpayer compliance, particularly among individual taxpayers, as indicated by the persistent gap between the number of registered taxpayers and those actively fulfilling their tax obligations. This situation indicates that increasing compliance does not solely depend on existing policies but is also influenced by various other internal and external factors. This study aims to analyze the factors influencing individual taxpayer compliance through a literature review approach, focusing on tax literacy, the use of information technology, and the implementation of the CoreTax Administration System (CTAS). The method used is to examine and synthesize various relevant previous studies to gain a more comprehensive understanding. The results of the study indicate that tax literacy plays a significant role in increasing taxpayer understanding and awareness, the use of information technology can provide convenience, efficiency, and accessibility in the tax process, while the implementation of CTAS contributes to increasing transparency and data integration within the tax administration system. Overall, these three aspects are interrelated and play a role in forming a more effective tax ecosystem in encouraging optimal and sustainable improvements in taxpayer compliance.